Interferência binaural e adaptação de próteses auditivas em perdas auditivas simétricas - Azevedo, Milena Manoel de (2013)
Purpose: To investigate the occurrence of binaural interference. To investigate the mono or binaural use of hearing aids and the complaints of speech comprehension in silence and noise.To evaluate the speech recognition with and without the use of mono and binaural hearing aids and the auditory processing skills.To correlate the obtained results in different tests. To evaluate the recognition of sentences in silence and noise by elderly individuals with symmetrical hearing loss, users of hearing aids with mono and binaural adaptation, and to investigate in which of both situations it may be verified the best performance in conditions that simulate daily communication situations. Material and Method: The evaluated subjects were 25 men and 13 women, with ages between 60 and 89 years old, with sensorineural hearing loss from mild to moderate severe level, symmetrical configuration, users of hearing aids with binaural indication. It was researched the Percentage Index of Speech Recognition (PISR) in both ears (BE) and it was performed the Dichotic Digits Test (DDT) of divided and directed attention, and the Portuguese Sentence List test (PSL). It was also studied the sentence recognition threshold in quiet (SRTQ) and in noise (SRTN) and the percentual indexes of sentence recognition in quiet environment and under noise (PISRQ and PISRN), with binaural adaptation (BA) and monaural in the right ear (RE) and in the left ear (LE). Results: Among the evaluated individuals, 31 (81.58%) referred that they use binaural hearing aids, 19 subjects (50%) reported they have never had difficulties to understand speech in silent places and 17 (44.75%) answered sometimes. 22 (57.89%) referred difficulties to recognize speech in noisy places, sometimes and 15 (39.47%) said it always happened. The obtained average values for the PISR were 72.95% in BE, 59.26% in the RE and 60.53% in the LE, respectively. The obtained averages in the DDT were 54.58% in BE, 65.16% in the RE and 71.95% in the LE. Regarding the PISRQ data, they were 79.63% in BE, 74.79% in the RE and 72.40% in the LE. The correlation of the PISR, DDT and PISRQ, the PISR and the PSL tend to present similar values. About analyzes into silence and into noise with binaural and monaural adaptation, the average values for PISRQ were 80.89% in BE, 76.33% in the RE and 71.16% in the LE, respectively. The obtained averages for PISRN were 62.05% in BE, 60.52% in the RE and 60.33% in the LE. Conclusion: It was found in an individual, the presence of binaural interference. Most elderly people used binaural hearing aids; only one individual did not present complaints of speech comprehension into noise. The PISR showed better performance in binaural condition; the DDT may not be the most proper option to be used in elderly patients with hearing loss; the PISR and the PSL tend to present similar values. The sentence recognition by the evaluated subjects presented better performance with the binaural adaptation, as into silence as into noise. However, that difference was not statistically significant.